Becoming a subject - Cavell, Marcia (Clarendon Press,Oxford University Press, 2006)
Marcia Cavell draws on philosophy, psychoanalysis, and the sciences of the mind in a fascinating and original investigation of human subjectivity. A "subject" is a creature, we may say, who recognizes herself as an "I", taking in the world from her own subjective perspective; who is an agent, doing things for reasons, sometimes self-reflective, and able to assume responsibility for herself and some of her actions. The idea of a 'subject' points, then, toward an ideal. It asks for the conditions under which a human infant becomes a subject, and for the sorts of things, like self-deception and massive anxiety, that get in the way